Геоінжинірингове забезпечення дослідження трансформації систем природокористування в Україні - Шевченко, Р.Ю. (Екологічна безпека та природокористування, 2012)
In article are discussed questions of the particularities of the using of geoengineering in engineering-cartographic technology in practical person rational of use of the nature. It is presented of terminological argumentation of studies, classification of map, is shown of designed algorithm of the introduction corresponding to methods, is determined of thematic contents of the electronic maps of the use of the nature.